Making memories: Chinese foodscapes, medicinal foods, and generational eating. (October 2020) - Chen, Nancy N
The availability and abundance of foods in 21st century China have dramatically expanded over the past three decades. Despite the proximity of memories of food insecurity—the intergenerational preparation and sharing of meals continue to mark social identity and belonging. This article explores how contemporary Chinese foodways and medicinal recipes connect with past times as well as convey cultural memory. Two case studies will animate this analysis. The first part of the article will examine the Cuisine Museum in Hangzhou where past coexists with present and future as attendees view displays of specific dishes and grand tables followed by consuming sumptuous meals recreated at the adjoining restaurant. The second half will explore the realms of medicinal foods and recipes that reflect longstanding notions of health that are being promoted in contemporary China. Altogether, these arenas suggest that foodscapes, particularly medicinal foods, offer key assemblages of food memory, time, and wellbeing.